Ideology, culture, and translation. - Boer, Roland, 1961-; Elliott, Scott S. (Atlanta Society of Biblical Literature, 2012)
"Translation is a fundamental aspect of biblical scholarship and an ever-present reality in a global context. Scholars interested in more than linguistically oriented translation problems of a traditional nature often struggle to find an interdisciplinary venue in which to share their work. These essays, by means of critical engagement with the translation, translation practices, and translation history of texts relevant to the study of Bible and ancient and modern Christianity, explore theoretical dimensions and contemporary implications of translations and translation practice."--Publisher description.
Chiefly in English, with one contribution in Spanish.
Keywords: Biblia -- Translating -- History and criticism; 22.05*5 -- Bijbel: vertalingsproblematiek; 22.06 <09> -- Bijbel: exegese--<geschiedenis>